The usefulness of a Happy Income Index - Aloys Prinz; Björn Bünger (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2011)
In this paper, Happy Income is introduced as an indicator of physical and socio-psychic wellbeing. It is constructed on the assumption that socio-economic well-being is based on objective circumstances, such as personal income as well as on a subjective evaluation of life. In combining these factors, Happy Income is a cardinal measure of overall well-being in a given country. Therefore, Happy Income is not subject to the limitations of purely ordinally scaled indicators, i.e. it is not restricted by an upper bound, which may be one explanation of the Easterlin paradox. The Happy Income concept is employed to measure social well-being in various different European countries. The results are compared to these countries' score on Ruut Veenhoven's Happy Life Years. It is argued that Happy Income is a valuable complement to other indicators of well-being at an aggregated level.
Keywords: I10; I31; 330; Happiness research; Happy Income; Happy Life Years; Subjective Well-being